Scleroderma Renal Crisis as Initial Presentation of Scleroderma - Sahil Bagai; Scienthia Sanjeevani; Dinesh Khullar; Bhavna Bansal; Vipra Malik (Indian Journal of Medical Specialities)
Scleroderma renal crisis (SRC) is characterized by the development of severe or worsening arterial hypertension associated with the abrupt onset of progressive renal failure in the absence of any other cause. Only 1% of limited and 4–11% of diffuse scleroderma cases have SRC. We report a case of SRC as an initial presentation in a newly diagnosed case of scleroderma.